2017
DOI: 10.1002/brb3.721
|View full text |Cite
|
Sign up to set email alerts
|

Picture free recall performance linked to the brain's structural connectome

Abstract: IntroductionMemory functions are highly variable between healthy humans. The neural correlates of this variability remain largely unknown.MethodsHere, we investigated how differences in free recall performance are associated with DTI‐based properties of the brain's structural connectome and with grey matter volumes in 664 healthy young individuals tested in the same MR scanner.ResultsGlobal structural connectivity, but not overall or regional grey matter volumes, positively correlated with recall performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…It is well‐established that successful memory retrieval requires the conjunct activation of a network of brain regions (Dickerson & Eichenbaum, 2010 ; Ritchey & Cooper, 2020 ; Rugg & Vilberg, 2013 ) further supporting the benefit of a higher interconnectedness and less functional segregation. Thus, these findings complement our previous results (Spalek et al, 2015 ) as well as existing literature (Coynel et al, 2017 ; Tunç et al, 2016 ) by providing a neuronal link for the observed memory advantage of females compared to males. Specifically, we previously identified differences between females and males in emotional episodic memory in a large sample (>3000 subjects).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well‐established that successful memory retrieval requires the conjunct activation of a network of brain regions (Dickerson & Eichenbaum, 2010 ; Ritchey & Cooper, 2020 ; Rugg & Vilberg, 2013 ) further supporting the benefit of a higher interconnectedness and less functional segregation. Thus, these findings complement our previous results (Spalek et al, 2015 ) as well as existing literature (Coynel et al, 2017 ; Tunç et al, 2016 ) by providing a neuronal link for the observed memory advantage of females compared to males. Specifically, we previously identified differences between females and males in emotional episodic memory in a large sample (>3000 subjects).…”
Section: Discussionsupporting
confidence: 92%
“…The association between episodic memory and structural brain connectivity has so far been investigated mainly in relation with aging (Fjell et al, 2016 ). Only one study (Coynel et al, 2017 ) has investigated the association between individual episodic memory performance and the level of structural brain connectivity in healthy young subjects. Additionally, Tunç et al, 2016 were able to distinguish males from females using connectivity as well as behavioral classifiers (derived from performance on a neurocognitive battery including memory tasks).…”
Section: Introductionmentioning
confidence: 99%
“…Activity in this region is augmented for selective attention relative to predict behavioral outcome (Jor’dan et al ., 2017). Free recall performance also activates temporal pole and nucleus accumbens region, with some unique memory-specific connections (Coynel et al ., 2017). Moreover, the frontoparietal cortex and visual regions activities are greatest when changing task sets (Lamichhane et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%